Seagrass ecosystems as habitats for target fish (Siganidae and Lethrinidae) in the waters of the Aruri Islands, Papua Province, Indonesia - SELVI TEBAIY; JEMMY MANAN; EMANNUEL MANANGKALANGI; SAMPARI S. SURUAN; DENNY C. MAMPIOPER; PHILIPUS MUSYERI; AGNESTESYA MANUPUTTY; DODI SAWAKI (Society for Indonesian Biodiversity, 2025)
Abstract. Tebaiy S, Manan J, Manangkalangi E, Suruan SS, Mampioper DC, Musyeri P, Manuputty A, Sawaki D. 2025. Seagrass ecosystems as habitats for target fish (Siganidae and Lethrinidae) in the waters of the Aruri Islands, Papua Province, Indonesia. Biodiversitas 26: 5726-5736. This study aimed to identify seagrass species, analyze their composition, percentage, and average cover, and determine the distribution and composition of fish species within seagrass ecosystems. Additionally, the relationships among various species and the presence of target fish, namely Siganidae and Lethrinidae, were examined. The research was conducted from November to December 2022 at three locations: Rayori Village, Nyambarai Village, and Munsaki Island in the Aruri Islands, Supiori District, Papua Province, Indonesia. Seagrass sampling employed the quadrat transect method modified from the Seagrass Watch protocol, while fish samples were collected using gill nets with the circle method. The results revealed the presence of six seagrass species in the study area, namely Cymodocea rotundata, Enhalus acoroides, Halodule pinifolia, Halophila ovalis, Oceana serrulata, and Thalassia hemprichii. Target fish, Siganus sp. and Lethrinus sp. were found at all observation sites, with 139 and 9 individuals, respectively. Furthermore, T. hemprichii showed a clear relationship with the presence of Siganus sp. and Lethrinus sp. indicating its essential role in seagrass ecosystems as a habitat for these target fish species. This study's findings underscore the crucial role of T. hemprichii in seagrass ecosystems and its implications for the conservation of these vital habitats in the Supiori District.